2021
DOI: 10.1016/j.bpj.2021.06.038
|View full text |Cite
|
Sign up to set email alerts
|

The membrane transporter lactose permease increases lipid bilayer bending rigidity

Abstract: Cellular life relies on membranes, which provide a resilient and adaptive cell boundary. Many essential processes depend upon the ease with which the membrane is able to deform and bend, features that can be characterized by the bending rigidity. Quantitative investigations of such mechanical properties of biological membranes have primarily been undertaken in solely lipid bilayers and frequently in the absence of buffers. In contrast, much less is known about the influence of integral membrane proteins on ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The influence of integral membrane proteins, such as lactose permease (LacY), egg lecithin (EYPC), and N-terminal low complexity domain of fused in sarcoma (FUS LC), on the bending rigidity of lipid bilayers under physiological conditions was investigated. 17,171 Regardless of the ionic strength, the bending rigidity of the membrane containing LacY was higher than that of the membrane without LacY. In Fig.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The influence of integral membrane proteins, such as lactose permease (LacY), egg lecithin (EYPC), and N-terminal low complexity domain of fused in sarcoma (FUS LC), on the bending rigidity of lipid bilayers under physiological conditions was investigated. 17,171 Regardless of the ionic strength, the bending rigidity of the membrane containing LacY was higher than that of the membrane without LacY. In Fig.…”
Section: Resultsmentioning
confidence: 83%
“…15(B), it is clear that the bending rigidity of the membrane containing LacY increased significantly, going from 25 k B T (in the absence of LacY) to a value above 40 k B T , specifically, the value is 43 k B T for PBS 40 : 40 : 20 and 41 k B T for NaPhos 40 : 40 : 20 when LacY is present in the membrane. 17…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, these proteins embedded in the plasma membrane could serve as specific receptors for binding NMs, or form specific domains which strengthen the rigidity of plasma membrane. [38] Wang et al reported that artificial phospholipid bilayer might capture the electrostatic interaction with similar responses as plasma membranes, but the integrity of artificial phospholipid bilayer is much more vulnerable than the plasma membrane. [39] After the adsorption of NMs on the plasma membrane, the adhesion strength needs to go over the energy barrier composed of binding energy and stretching energy to drive the internalization of NMs.…”
Section: The Theory For Cellular Internalization Of Nmsmentioning
confidence: 99%